Discovery of dense aggregations of stalked crinoids in Izu-Ogasawara trench, Japan - Oji, T.; Ogawa, Y.; Hunter, Aaron; Kitazawa, K. (Nihon Dobutsu Gakkai, 2009)
Stalked crinoids are recognized as living fossils that typically inhabit modern deep-water environments exceeding 100 m. Previous records of stalked crinoids from hadal depths (exceeding 6000 m) are extremely rare, and no in-situ information has been available. We show here that stalked crinoids live densely on rocky substrates at depths over 9000 m in the Izu-Ogasawara Trench off the eastern coast of Japan, evidenced by underwater photos and videos taken by a remotely operated vehicle. This is the deepest in-situ observation of stalked crinoids and demonstrates that crinoid meadows can exist at hadal depths close to the deepest ocean floor, in a fashion quite similar to populations observed in shallower depths. ©2009 Zoological Society of Japan.